2022
DOI: 10.1177/14644207221102514
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-electrical performance of hybrid busbars: An experimental and numerical investigation

Abstract: This paper is focused on hybrid busbars made from aluminum and copper with the purpose of analyzing the influence of temperature on the electric performance of the joints. The methodology involves the fabrication of fastened, friction stir spot welded, sheet-bulk compressed, and injection lap riveted unit cells that are representative of the different types of hybrid busbars joints, the development of a special purpose laboratory apparatus for thermo-electrical measurements, and numerical simulation with a fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The effectiveness of the riveted joint is also proved by the fact that although the overlapped contact length L is half of that utilized in the fastened joint [21], the differences in the measured electrical resistance are not significant, which indicates an increased contact area produced by the riveted joint, which is responsible for compensating for the significant reduction in the contact length. Also, it was seen in [21] that the tightening torque of the bolt and nut in the fastened joint has a substantial impact on the contact pressure and consequently on the electrical resistance, which can be severely compromised by the self-loosening of the fastened joint during its service life.…”
Section: Electrical Performancementioning
confidence: 97%
See 1 more Smart Citation
“…The effectiveness of the riveted joint is also proved by the fact that although the overlapped contact length L is half of that utilized in the fastened joint [21], the differences in the measured electrical resistance are not significant, which indicates an increased contact area produced by the riveted joint, which is responsible for compensating for the significant reduction in the contact length. Also, it was seen in [21] that the tightening torque of the bolt and nut in the fastened joint has a substantial impact on the contact pressure and consequently on the electrical resistance, which can be severely compromised by the self-loosening of the fastened joint during its service life.…”
Section: Electrical Performancementioning
confidence: 97%
“…The specimens were subjected to different tests to analyse the mechanical and electrical performance of the mechanical joint. The latter is evaluated by means of the evolution of the electrical resistance with different working temperatures ranging from 16 • C to 100 • C. Comparisons are then made with fastened Al-Cu busbar connections [20,21] to evaluate and discuss the gains resulting from the utilization of DSSPR to produce busbar connections.…”
Section: Introductionmentioning
confidence: 99%
“…In energy distribution systems, for example, the commonly used solutions are based on mechanical or thermal based processes involving bolting, laser welding, or friction stir spot welding, but the overall thermo-electrical performance of the resulting joints is much lower than that of an ideal joint. In fact, in a recently published work [10], the authors showed that the electrical resistance of bolted (with 20 Nm torque) and friction stir spot-welded joints of hybrid busbars made from aluminum and copper sheets are 1.4 and 1.6 times higher than that of an ideal joint. This difference increases during service life due to chemical reactions, contaminant films, and unintentional self-loosening that reduces the contact pressures on the overlapped surfaces [11,12].…”
Section: Introductionmentioning
confidence: 99%